1997
DOI: 10.1023/a:1018550307649
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Tendon and corneal decorins are differently iduronated dermatan sulphate/proteoglycan (DS/PG) and the biochemical parameter that differentiates type I collagens is the hydroxylysine glycoside content. We have examined the effect of tendon and corneal decorins on the individual phases (tlag, dA/dt) of differently glycosylated type I collagens fibril formation, at molar ratios PG:collagen monomer ranging from 0.15:1 to 0.45:1. The results obtained indicate that decorins exert a different effect on the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Notably, the amount of DCN on beads that was required to produce inhibition of collagen binding by cells was very low (3 ϫ 10 Ϫ20 mol of DCN bound/bead) and approached an equimolar ratio (0.34) with the amount of collagen on beads (8.7 ϫ 10 Ϫ20 mol of collagen bound/bead). DCN and Collagen Binding-Previous studies on DCN-collagen interactions have largely focused on modulation of collagen fibrillogenesis (9,10,20,(32)(33)(34). The novelty of the current report is that DCN inhibits the collagen binding step of phagocytosis as demonstrated by a consistent and marked reduction in collagen bead binding.…”
Section: Discussionmentioning
confidence: 73%
“…Notably, the amount of DCN on beads that was required to produce inhibition of collagen binding by cells was very low (3 ϫ 10 Ϫ20 mol of DCN bound/bead) and approached an equimolar ratio (0.34) with the amount of collagen on beads (8.7 ϫ 10 Ϫ20 mol of collagen bound/bead). DCN and Collagen Binding-Previous studies on DCN-collagen interactions have largely focused on modulation of collagen fibrillogenesis (9,10,20,(32)(33)(34). The novelty of the current report is that DCN inhibits the collagen binding step of phagocytosis as demonstrated by a consistent and marked reduction in collagen bead binding.…”
Section: Discussionmentioning
confidence: 73%
“…It co-localizes with large helical collagen fibers 15 and binds specific sites on collagen molecules as they assemble, thereby increasing the tensile strength of uncross-linked collagen fibers. 16 Decorin null mice have more severe LV dilation after experimentally-induced myocardial infarction. 17 In MR dogs, decorin mRNA downregulation correlated with the increase in LVEDD (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported on the influence of SLRPs on collagen fibril formation in vitro . Decorin, for example, was shown to influence the fibrillogenesis rate as well as the diameter of collagen fibrils . While fibrillogenesis rate is thought to be mediated by both, the core protein as well as the chondroitin (CS)/dermatan sulfate chain in decorin, the regulation of the diameter was found to be particularly dependent on the glycosaminoglycan (GAG) part and its iduronic acid content …”
Section: Introductionmentioning
confidence: 99%
“…[5] Decorin, for example, was shown to influence the fibrillogenesis rate as well as the diameter of collagen fibrils. [9][10][11][12] While fibrillogenesis rate is thought to be mediated by both, the core protein as well as the chondroitin (CS)/dermatan sulfate chain in decorin, [9,12] the regulation of the diameter was found to be particularly dependent on the glycosaminoglycan (GAG) part and its iduronic acid content. [9,13] The influence of GAGs on the in vitro-fibrillogenesis of collagen has been studied since the 1960s.…”
Section: Introductionmentioning
confidence: 99%